2010
DOI: 10.1002/ps.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acetochlor sorption and degradation in limestone subsurface and aquifers

Abstract: Sorption was weak in limestone and aerobic sandy aquifers, and strong in topsoils and in reduced sandy aquifers. Redox conditions controlled the extent of acetochlor sorption in aquifers, as reduced conditions induced increased sorption. Acetochlor was mineralised in deep subsurface, though slowly, and, as mineralisation is the only true removal mechanism in natural attenuation, even slow mineralisation in aquifers with long residence times can have a significant impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…However, isoproturon was also mineralized in water from the spring (25-41%, data not shown). Acetochlor was not mineralized in any of the groundwater samples (data not shown) though mineralization has been reported previously in aquifer samples from the catchment (Janniche et al, 2010b). The herbicide mineralization ability observed in groundwater from Pz5 is in accordance with this being the most agriculturally affected sample.…”
Section: Mineralization Abilitysupporting
confidence: 88%
“…However, isoproturon was also mineralized in water from the spring (25-41%, data not shown). Acetochlor was not mineralized in any of the groundwater samples (data not shown) though mineralization has been reported previously in aquifer samples from the catchment (Janniche et al, 2010b). The herbicide mineralization ability observed in groundwater from Pz5 is in accordance with this being the most agriculturally affected sample.…”
Section: Mineralization Abilitysupporting
confidence: 88%
“…Acetochlor binds strongly to organic matter in the soil (Hiller et al, 2008), which makes it unlikely to leach into groundwater. Additionally, studies have shown that acetochlor is readily degradable in topsoil and in the subsurface (Janniche et al, 2010). Accordingly, it has only rarely been detected in surface water and groundwater (Barbash et al, 1999;Kolpin et al 1996).…”
Section: Applied Pesticides In the Ncp And Their Potential Environmenmentioning
confidence: 99%
“…Acetochlor [2‐chloro‐N‐(ethoxymethyl)‐N‐(2‐ethyl‐6‐methylphenyl) acetamide] is a chloroacetanilide herbicide that is mostly used to control pre‐emergent grass weeds in various cropping systems. Acetochlor has a high water solubility of 223 mg L −1 and a vapor pressure of 4.5 × 10 −3 mPa (Janniche et al, 2010). The reported half‐life of acetochlor ranges from 4.6 to 9.3 d in surface soils (Ye, 2003; Taylor et al, 2005; Oliveira et al, 2013).…”
mentioning
confidence: 99%